MAKNA SIMBOLIK TRADISI TUWUN MANDI DI DESA PANGKALAN INDARUNG KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Riko Muriono; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Tuwun Mandi is one of the traditions of the village of Pangkalan Indarung located in Singingi District, Kuantan Singingi Regency. This tradition is held as a welcome for newborns. Which helps as a way for the baby to get acquainted with the world. The purpose of this research is to study the symbolic meaning that exists in this tradition, while the subfocus is the symbolic meaning of competition in the Tuwun Mandi tradition, the product of interaction from the Tuwun Mandi tradition, and the interpretation of the Tuwun Mandi tradition. This study used qualitative research methods. The informants of this study were determined based on a purposive technique, which consisted of 2 core implementers and 3 general public meaning that all informants in this study had been selected based on certain considerations. Data collection techniques used were observation, interviews, and documentation. The data validity technique used in this study is triangulation and extension of participation. The results of this study indicate that, the meaning of the physical object that is all the attributes used such as incense: the prayer will start, chicken: a substitute for life in the hereafter, a knife: a weapon in life, a pot of pot: a barrier to disease and others. social object that is mantra: blessed by the ancestors and prayer: blessing from the almighty god. The meaning of social interaction products for traditional leaders: the identity of the Indarung base community, village midwives: preserving cultural heritage and the general public: so that children get blessed. The meaning of interpretation includes closed actions and open actions. Closed actions are related to motivation and feelings. The open act is a happy facial expression. Keywords : symbolic meaning, tradition